Memanfaatkan One Belt One Road: Kepentingan Ekonomi Pakistan dalam China-Pakistan Economic Corridor Tahun 2015-2020 - Aryaguna, Addafi; Windiani, Reni (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2021)
Under the One Belt One Road scheme, China-Pakistan Economic Corridor (CPEC) is a series of massive infrastructure project that are under construction in Pakistan that consists of transportation network construction, energy projects, storage facilities, port, SEZs, and other elements under the CPEC banner worth 46 Billion US. But the CPEC projects came at a huge risk for Pakistan, as the investment aid from China came in the form of a loan, and the and that the security of CPEC projects are under threat from separatist groups like the BLA. This research’s purpose is to find out the reason behind Pakistan's agreement to conduct a bilateral cooperation with China under the CPEC projects in the period of 2015-2020. This research would employ the liberalism paradigm as the analytic tool. This study hypothesizes that the reason for Pakistan's willingness to cooperate with China is the existence of its domestic economic interests despite of its controversies. The results of this study indicate that Pakistan does have a strong desire to develope its domestic economy, while CPEC plays an important role in this process. In addition, the CPEC was also viewed by Pakistan as a cooperation that could support this country to achieve the Pakistan Vision 2025.